Respostas
respondido por:
16
Resposta:
Alternativa C)
Explicação passo-a-passo:
cos (a + b) = (cosa)cosb - (sena)(senb)
cos (a - b) = (cosa)cosb + (sena)(senb)
(a + b)(a - b) = a² - b²
cos15 ⇒ cos(45 - 30) ⇒ cos45cos30 + sen45sen30
cos75 ⇒ cos(45 + 30) ⇒ cos45cos30 - sen45sen30
cos15.cos75 ⇒ cos²45cos²30 - sen²45sen²30
[(√2)/2]²[(√3)/2]² - [(√2/2)]²[(1/2)]²
( 2/4)(3/4) - (2/4)(1/4)
6/16 - 2/16
4/16
1/4
y = 4cos15cos75
y = 4[1/4]
y = 1
y² = 1² ⇒ y² = 1
Alternativa C)
seidenada912:
Obrigada
Perguntas similares
5 anos atrás
5 anos atrás
5 anos atrás
7 anos atrás
8 anos atrás
8 anos atrás